Sunrise canyon - Dailey, Janet (New York : Zebra Books, 2017)
Though hesitant to expose his daughter to the man war turned him into, Jake O'Reilly agrees to work on the ranch where his daughter is living. There he meets, Kira, his late wife's cousin, who runs a horse therapy program for troubled teens. Though Jake doesn't want any complications in his life, he finds himself drawn to the tough Kira and begins to feel his wounds finally start to heal.
Keywords: Ranch life -- Fiction; Love stories